Trends and Development of Digital Learning Research to Train Science Literacy in Physics Learning: Literature Review and Bibliometric Analysis - Wardi, Ladika Zuhrotul; Wasis, Wasis; Widodo, Wahono; Satriawan, Muhammad; Nisa, Khoirun (FKIP Universitas Lampung, 2024)
In the current era, the ability to face the challenges posed by advances in science and technology is needed. One of the skills needed is science literacy. The development of technology affects the world of education, namely the development of digital learning. This study aims to provide an overview of trends, methods, and research findings related to digital learning in training science literacy in physics learning. The method used in this research is Systematic Literature Review (SLR) with the help of visualization using vosviewer software. Article data for the last 10 years (2014-2023) were collected from the Scopus database, with 10 articles selected using the PRISMA technique and bibliometric analysis. Quantitative and qualitative analysis techniques were used. Research on digital learning to train science literacy skills has increased significantly over the past 10 years with Spain as the country with the most research contributions. Digital learning supports a lot in improving students' science literacy skills in physics learning. The focus of future research can also be directed at developing 21st century skills through digital learning media in various disciplines. Keywords: digital learning, science literacy, physics.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1051-1066